2
$\begingroup$

Let $H$ be a Hilbert space , If a continuous linear operator $T:H \to H$ has a bounded inverse $T^{-1}$ , then $T^{*}$ has a bounded inverse and $(T^*)^{-1}=(T^{-1})^*$

This theorem was in Michael Reed's functional analysis page $186$ .
I'm quite confused why we need to assume $T$ has a bounded inverse . If $T$ has an inverse $T^{-1}$ , then $T$ is necessarily bijective . In particular , $T$ is surjective . So by open mapping theorem on banach space , we conclude $T$ is an open mapping which means $T^{-1}$ is continuous . But on banach space , continuous is equivalent to bounded . So I don't understand why we need this assumption .

$\endgroup$
0
$\begingroup$

The assumptions make the proof easy. If $TS=ST=I$ where $T,S$ are bounded operators, then $S^*T^*=T^*S^*=I^*=I$ gives $(T^*)^{-1}=S^*=(T^{-1})^*$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.